Polarity effect of PD in oil-pressboard insulation under highly uneven electric field. (July 2020) - Li, Simeng; Wei, Zhenyu; Li, Qingquan; Wang, Peijin
Highlights: Non-uniform electric field simulated by a needle-plate model. PD statistical feature, PD pattern and pulse under either AC or DC voltage studied. Charge distribution simulated considering the effects of interface charge. Explanation of underlying PD mechanisms through a PD circuit model. Cause of PD polarity effect analyzed based on PD mechanisms. Abstract: The polarity effect of the partial discharge (PD) in oil-pressboard (oil-PB) insulation under a highly non-uniform electric field is remarkable. For intensive analysis of the characteristics and mechanisms of this polarity effect, a non-uniform electric field was simulated by a needle-plate model with oil-PB composite insulation. The PD statistical features, PD pattern and PD pulse were studied via pulse current method, the charge distribution was simulated on the basis of hydrodynamic drift-diffusion model and bipolar charge transport model, and the cause of the polarity effect was analysed based on the PD mechanism which is quantificationally explained via a PD circuit model. It was found that the average apparent discharge amplitude and PD repetition rate of the neg-PD are higher; the average equivalent frequency and equivalent time of neg-PD are higher and lower respectively; the pos-PD pulse is unimodal and the neg-PD pulse is oscillating with some secondary discharges at AC voltage or a back discharge at DC voltage; and the neg-PD pulse has a narrower width owning to the fast rising edge and falling edge. The PD current pulse in the coupling loop is essentially caused by the charging process of the streamer-shorted defect. The cause of the polarity effect is that the positive streamer evolves slowly and can puncture the entire oil gap with an energy-concentrated channel, whereas the negative streamer with a diffused channel evolves faster but cannot puncture the entire oil gap.